The United States and Germany during the twentieth century: competition and convergence - Mauch, Christof; Patel, Kiran Klaus (Cambridge University Press [u.a.], 2010)
"The United States and Germany during the Twentieth Century presents a wide ranging comparison of American and German societies during the late 19th and 20th centuries"--
Includes bibliographical references and index
Keywords: Deutschland; USA; Aufsatzsammlung; Geschichte